The total money makeover ebook Classic edition: a proven plan for financial fitness. - Ramsey, Dave (2013)
Do you want to build a budget that actually works for you? Are you ready to transform your relationship with money? This New York Times bestseller has already helped millions of people just like you learn how to develop everyday money-saving habits with the help of America's favorite personal finance expert, Dave Ramsey. By now, you've already heard all of the nutty get-rich-quick schemes and the fiscal diet fads that leave you with a lot of quirky ideas but not a penny in your pocket. If you're tired of the lies and sick of the false promises, Dave is here to provide practical, long-term help. The Total Money Makeover is the simplest, most straightforward game plan for completely changing your finances. And, best of all, these principles are based on results, not pie-in-the-sky fantasies. This is the financial reset you've been looking for. The Total Money Makeover: Classic Edition will give you the tools and the encouragement you need to: Design a sure-fire plan for paying off all debt—from your cars to your home and everything in between using the debt snowball method Break bad habits and make lasting changes when it comes to your relationship with money Recognize the 10 most dangerous money myths Secure a healthy nest egg for emergencies and set yourself up for retirement Become financially healthy for life Live like no one else, so later you can LIVE (and GIVE) like no one else! This edition of The Total Money Makeover includes new, expanded "Dave Rants" that tackle marriage conflict, college debt, and so much more. The Total Money Makeover: Classic Edition also includes brand new back-of-the-book resources to help you make The Total Money Makeover your new reality.